Biochemistry and Health Benefits of Fatty Acids - Waisundara, Viduranga (Biochemistry, 2018)
Fatty acids are considered as a very important category of chemical compounds to human health as well as from an industrial perspective. This book intends to provide an update on fatty acid research, their methods of detection, quantification, and related diseases such as cardiovascular disease and diabetes. Cyclic fatty acids are also covered, along with short chain fatty acids, which are important to the human gut microbiota. Fatty acids are important in the chemical structure of the cell membrane and its pivotal role in this aspect is reviewed herein. The book also contains a chapter that deals with some unpublished molecular aspects concerning the roles of fatty acids in depression and bipolar disorder. All in all, the book provides a brief overview of both highly explored as well as overlooked perspectives of fatty acids, while highlighting its significance as a biochemical molecule, which is imperative to the livelihood of unicellular and multi-cellular organisms alike.